2021
DOI: 10.1007/s00395-021-00887-3
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LncHrt preserves cardiac metabolic homeostasis and heart function by modulating the LKB1-AMPK signaling pathway

Abstract: Metabolic modulation is a promising therapeutic approach to prevent adverse remodeling of the ischemic heart. Because little is known about the involvement of long non-coding RNAs (lncRNAs) in regulating cardiac metabolism, we used unbiased transcriptome profiling in a mouse model of myocardial infarction (MI). We identified a novel cardiomyocyte-enriched lncRNA, called LncHrt, which regulates metabolism and the pathophysiological processes that lead to heart failure. AAV-based LncHrt overexpression protects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 74 publications
(106 reference statements)
0
20
0
Order By: Relevance
“…Moreover, LKB1 may participate in the regulation of ER stress and autophagy of macrophages through other pathways ( Khayati et al, 2020 ; Zuo et al, 2020 ). With the deepening of understanding, the pathophysiological value of LKB1 in cardiovascular and metabolic diseases has attracted much attention ( Liang et al, 2021 ; Liu et al, 2021 ). It has been observed that LKB1 expression is down-regulated in atherosclerotic macrophages and is involved in the regulation of atherosclerosis ( Liu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LKB1 may participate in the regulation of ER stress and autophagy of macrophages through other pathways ( Khayati et al, 2020 ; Zuo et al, 2020 ). With the deepening of understanding, the pathophysiological value of LKB1 in cardiovascular and metabolic diseases has attracted much attention ( Liang et al, 2021 ; Liu et al, 2021 ). It has been observed that LKB1 expression is down-regulated in atherosclerotic macrophages and is involved in the regulation of atherosclerosis ( Liu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA cardiomyocyte-enriched non-coding transcript (Caren) preserves cardiac function during pressure overload by suppressing the ataxia telangiectasia mutated (ATM)/DNA damage response (DDR) pathway, thus maintaining mitochondrial biogenesis and function ( 35 ). LncHrt modulates the deacetylase activity of sirtuin 2, which enhances the oxidative phosphorylation (OXPHOS) capacity of mitochondria, thereby preserving cardiac metabolic homeostasis and function ( 36 ).…”
Section: Roles Of Lncrnas In the Pathogenesis Of Hfmentioning
confidence: 99%
“…It has been well established that lncRNAs play an important role in myocardial infarction (MI)-induced cardiac fibrosis and HF, such as lncRNA-Safe ( 74 ), LncHrt ( 36 ), Wisp2 super-enhancer-associated RNA (Wisper) ( 75 ), and cardiac fibroblast-associated transcript (Cfast) ( 76 ). All of them are enriched in fibroblasts.…”
Section: Roles Of Lncrnas In the Pathogenesis Of Hfmentioning
confidence: 99%
“…LncRNAs are now known to exert influence on diverse biological processes, such as cell cycle ( Guiducci and Stojic, 2021 ), proliferation ( Liu et al, 2021 ), metastasis ( Hong et al, 2021 ), and differentiation ( Li. et al, 2021 ), as well as several diseases ( Li et al, 2021 ; Liu et al, 2021 ; Xin and Liu, 2021 ). Moreover, emerging evidence shows that lncRNAs participate in the osteogenic differentiation of BMSCs.…”
Section: Lncrnas and Osteogenic Differentiation Of Bmscsmentioning
confidence: 99%